Oxytocin protects against sepsis-induced multiple organ damage: Role of neutrophils - YEGEN, BERRAK; ERCAN, FERİHA; ŞENER, GÖKSEL (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2005)
Background. Sepsis, commonly associated with enhanced generation of reactive oxygen metabolites, leads to multiple organ dysfunctions. The neurohypophyseal hormone oxytocin (OT), released during social contact, was recently shown to modulate the immune and inflammatory processes. We investigated the protective role of OT against sepsis-induced pelvic inflammation. Materials and methods. Under anesthesia, sepsis was induced in female Sprague-Dawley rats (200-250 g) by cecal ligation and perforation method. Sham-operated rats served as controls. Either saline or OT (1 mg(kg) was given subcutaneously immediately after and at the 16th hour, and rats were decapitated at the 24th hour of sepsis induction. Colon, uterus, and liver samples were obtained for the histopathological analysis of damage and for the measurement of myeloperoxidase (MPO) activity, indicating neutrophil infiltration, malondialdehyde (AIDA), indicating lipid peroxidation, and glutathione (GSH), a key antioxidant, levels. Results. Colonic, uterine and liver MDA levels in the sepsis group were significantly increased (P < 0.01-P < 0.001), while colonic and uterine GSH levels were decreased (P < 0.05-P < 0.01) when compared to the control group. OT treatment reversed the MDA and GSH levels back to the control levels, while hepatic GSH levels were not altered. MPO activity in the colon and liver was increased by sepsis (P < 0.05-P < 0.001) while OT treatment abolished the elevated MPO activity. Collagen levels in the uterus and liver were increased by sepsis (P < 0.01) and OT treatment reduced the collagen levels in both tissues (P < 0.01-P < 0.05). Serum TNF-alpha levels were significantly increased by sepsis (P < 0.001) and OT treatment abolished the sepsis-induced increase in TNF-alpha levels. Conclusions. OT protects against sepsis-induced oxidative damage by acting as an antioxidant agent and its protective effect in the colon and liver appears to be dependent on its inhibitory effect on neutrophil infiltration. Our results suggest that OT may have a therapeutic value in limiting sepsis-associated multiple organ damage. (C) 2005 Elsevier Inc. All rights reserved.
Keywords: oxytocin; sepsis; myeloperoxidase; glutathione; TNF-alpha; MELATONIN TREATMENT; OXIDATIVE STRESS; GROWTH-HORMONE; SEPTIC SHOCK; INFLAMMATION; RAT; INJURY; PERITONITIS; LIPOPOLYSACCHARIDE; GLUTATHIONE